Implementasi Model Discovery Learning pada Pembelajaran IPA Kelas V Materi Manusia dan Lingkungan - Retno Anjar Risnawati; Idam Ragil Widianto Atmojo (SAP (Susunan Artikel Pendidikan), 2023)
Preliminary investigations at SDN Patik Pulung Ponorogo's fifth-grade science class disclosed that most students still struggle with understanding the subject matter. These initial findings paved the way for the present research. The issue lies in the teacher's lack of encouragement for students to engage actively in their learning journey. Consequently, fostering student engagement in learning becomes paramount. A beneficial scientific strategy is the implementation of the discovery learning model. The aim of this research is to outline the application of the Discovery Learning Model's components within the classroom setting. The research methodology employed is qualitative in nature. The findings revealed a commendable success in integrating the discovery learning model into the Class V science curriculum focusing on human and environmental topics at SDN Patik, in Pulung District, Ponorogo Regency (as per classroom activities). The execution of the discovery learning model facilitates students' comprehension of the topics and stimulates them to take an active part in their learning process.